Neonatal Urinary Tract Infection and Renal Nodular Lesion: A Rare Case of Xanthogranulomatous Pyelonephritis - Catarina Granjo Morais MD; Sara Gomes MD; Ana Catarina Fragoso PhD; Janine Coelho MD; Joana Jardim MD; João Luís Barreira MD; Irene Pinto-Carvalho MD; Helena Pinto MD (SAGE Publishing, 2022)
Xanthogranulomatous pyelonephritis (XPN) is an uncommon variant of chronic pyelonephritis with a poorly understood pathogenesis and a challenging diagnosis. It is rare in pediatric patients, particularly in the neonatal period. We report the case of an 18-day-old female neonate admitted to the emergency room due to macroscopic hematuria and poor feeding. Urinalysis revealed leukocyturia and she was initially admitted under the clinical suspicion of acute pyelonephritis. Renal ultrasound and magnetic resonance imaging (MRI) revealed a progressive nodular lesion in the middle third of the left kidney. Given the suspicion of renal abscess or neoplasm, the patient was transferred to our tertiary hospital. Urinary catecholamines and tumor markers had normal values. Percutaneous kidney biopsy confirmed XPN. Posterior computed tomography scan excluded extension to neighboring structures. A conservative management with systemic antibiotic therapy was decided. She completed 7 weeks of systemic antibiotic therapy (ampicillin and cefotaxime) with progressive reduction of lesion size and posterior calcification. Follow-up at 3 years was uneventful. The lipid profile and study of neutrophil function were normal. Voiding cystourethrography excluded vesicoureteral reflux. The authors intend to highlight the importance of a high index of suspicion of XPN to allow preoperative diagnosis. Histopathological assessment is mandatory to confirm XPN and exclude other entities mimicked by focal and unilateral progressive disease. There are only a few published cases of optimal clinical evolution solely with broad-spectrum antibiotics; however, this may allow a beneficial nephron-sparing approach in selected patients.